Differences In Price and Trading Volume of BCA Shares Before and After the Election Year 2024 In Indonesia - Eemy Nurbaety; Rohmadi Rohmadi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to examine the difference in the average share price and average trading volume of BCA shares between before and after the election in Indonesia on January 16 - March 14, 2024. This type of research is the study of events with a quantitative approach. The research data is secondary data in the form of stock price history and trading volume of BCA shares listed on the IDX. The sample in this study was 38 data consisting of 19 data before and 19 data after the 2024 election event held in Indonesia. The data analysis technique uses the Paired Sample t-test hypothesis test. The results showed that there was a difference in stock prices before and after the 2024 election in Indonesia and no difference in stock trading volume before and after the 2024 election in Indonesia. The conclusion of the study was obtained that investors received information about the 2024 election events in Indonesia as bad news because changes in stock trading volume occurred negatively and stock prices occurred positively which tended to be significant, causing a decrease in buying interest in investors.